Review on the Energy Storage Technologies with the Focus on Multi-Energy Systems - Vahid-Ghavidel, Morteza; Javadi, Sara; Gough, Matthew; Javadi, Mohammad S.; Santos, Sérgio F.; Shafie-khah, Miadreza; Catalão, João P.S. (Wiley-VCH Verlag, 2022)
Energy storage is an important element of an energy system. In the power system, energy storage can be defined as a component that can be employed to generate a form of energy or utilize previously stored energy at different locations or times when it is required. Energy storage can enhance the stability of the grid, increase the reliability and efficiency of integrated systems that include renewable energy resources, and can also reduce emissions. A diverse set of storage technologies are currently utilized for the energy storage systems (ESSs) in a varied set of projects. This chapter provides information about the current ESS projects around the world and emphasizes the leading countries that are developing the applications of ESSs. The main categories of ESSs are explained in this chapter as follows: electrochemical, electromechanical, electromagnetic, and thermal storage. Moreover, the energy storage technologies are utilized in power grids for various reasons such as electricity supply capacity, electric energy time-shifting, on-site power, electric supply reserve capacity, frequency regulation, voltage support, and electricity bill management. Additionally, by integrating the various energy forms and developing the concept of multi-energy systems, ESSs become a fundamental component for the efficient operation of multi-energy systems. The main role of ESSs in multi-energy systems is to compensate for the fluctuations in power output from renewable energy resources. Moreover, the performance of the multi-energy system increases when it got integrated with an ESS. In this chapter, the applied ESS technologies in the context of the multi-energy systems are presented and explained.
Keywords: Electrochemical; Electromechanical; Energy storage technologies; Multi-energy systems; Power systems; fi=Sähkötekniikka|en=Electrical Engineering|